2019
DOI: 10.3389/fimmu.2019.02212
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP-AMP Triggers Asthma in an IL-33-Dependent Manner That Is Blocked by Amlexanox, a TBK1 Inhibitor

Abstract: Extracellular host-derived DNA, as one of damage associated molecular patterns (DAMPs), is associated with allergic type 2 immune responses. Immune recognition of such DNA generates the second messenger cyclic GMP-AMP (cGAMP) and induces type-2 immune responses; however, its role in allergic diseases, such as asthma, has not been fully elucidated. This study aimed to determine whether cGAMP could induce asthma when used as an adjuvant. We intranasally sensitized mice with cGAMP together with house dust mite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…This implies that for half of the transcription factors at regions with decreased accessibility, there is both decreased accessibility of binding sites and decreased availability of transcription factors; for the other half there is increased availability of the corresponding transcription factor despite decreased accessibility of binding sites. Many of the transcription factors with enriched binding motifs at regions with RV-responsive chromatin have been implicated in studies of lung function (FOXP2 25 , EPAS1 26 , SP1 27 ), immune function (IRF1 28 , IRF2 29 , IRF3 30 , BCL6 31 , PRDM1 32 , FOXA3 33 , FOXO1 34 ), and asthma (CTCF 35 , HIF1A 36 , STAT4 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…This implies that for half of the transcription factors at regions with decreased accessibility, there is both decreased accessibility of binding sites and decreased availability of transcription factors; for the other half there is increased availability of the corresponding transcription factor despite decreased accessibility of binding sites. Many of the transcription factors with enriched binding motifs at regions with RV-responsive chromatin have been implicated in studies of lung function (FOXP2 25 , EPAS1 26 , SP1 27 ), immune function (IRF1 28 , IRF2 29 , IRF3 30 , BCL6 31 , PRDM1 32 , FOXA3 33 , FOXO1 34 ), and asthma (CTCF 35 , HIF1A 36 , STAT4 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…To some extent, our current findings on 2′3′-cGAMP are consistent with a new report showing that a bacterial cyclic dinucleotide, c-di-GMP, can effectively inhibit IL-33– or Alternaria -induced type 2 inflammation in mice ( 43 ). However, it has also recently been reported that in another model of allergic inflammation, the administration of 2′3′-cGAMP had an adjuvant effect that exacerbated the HDM-induced Th2 response ( 44 ). This result is contrast to our data presented in Supplemental Figure 7 , in which HDM-induced type 2 inflammation was attenuated by 2′3′-cGAMP administration.…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, IL-33 and ST2 mRNA and protein expression levels are very low in both human and mouse lung fibroblasts ( 19 , 96 , 97 ). IL-33 expression in lung fibroblasts can be upregulated in vitro by stimulation with TNF-α, TNF superfamily member 14 (also known as LIGHT), IL-1β, and second messenger cyclic GMP-AMP ( 19 , 97 , 98 ) and downregulated by interferon-γ ( 99 ). In vivo , IL-33 expression in lung fibroblasts is increased in mice with bleomycin-induced pulmonary fibrosis ( 56 ), and in patients with idiopathic pulmonary fibrosis ( 100 ).…”
Section: Il-33 and Lung Fibroblastsmentioning
confidence: 99%